Time-resolved photoluminescence of two-dimensional hot carriers in GaAs-AlGaAs heterostructures - Ryan, J; Taylor, R; Turberfield, A; Maciel, A; Worlock, J; Gossard, A; Wiegmann, W (1984)
We have studied the picosecond time dependence of luminescence from a two-dimensional electron system following absorption of an ultrashort light pulse. From our measurements we determine the temporal evolution of the carrier temperature, finding that the cooling of hot carriers is suppressed by a factor 60 below that predicted on a three-dimensional nondegenerate-electron model. Additionally, we determine the electron-hole radiative life-time and invoke a hole trap to explain shortened luminescence lifetimes at low carrier densities. © 1984 The American Physical Society.